(untitled) (Scientific journal of the Fergana State University, 2023)
The article spoke about the solid legal basis of the Uzbek language and that our state language, which has a decent status, is entering a new stage of development and formation. The decrees of the President of the Republic of Uzbekistan “On measures to radically increase the prestige and status of the Uzbek language as the state language” and “on measures for the further development of the Uzbek language and improvement of language policy in our country" were signed, the Department for the development of the state language in our country was established, as well as the concept of the development of the Uzbek language and improvement of language policy in 2020-2030 and a program for the implementation of this concept for 2020-2022 has been adopted, examples show, that the main directions of the development of the Uzbek language and the improvement of language policy have been identified, and the large-scale reforms carried out in this direction open up wide opportunities for the development of the state language.